Memahami Narasi Kisah al-Quran dengan Narrative Criticism (Studi atas Kajian A.H. Johns) - Wardatun Nadhiroh (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
The Quran had various styles and modes in making up Gods word, one of which was the narrative one. There were many narrative verses in the Quran -including verses telling stories of His prophets- to which most of Muslim scholars unfortunately did not devote their attention. A.H. Johns, a professor of ANU, was one of a few scholars who focused his study on narrative criticism that was actually one of branches of literary criticism. Unlike historical criticism which tended to investigate the origins of a text and what lied behind it, literary criticism gave much attention to interpretive acts of a text itself. Using this method of interpretation, and relying on his belief that the Quran must be understood as a both a process and an event, Johns explored possible meanings the verses imply by making connection between the verse under discussion and other verses in the same pericope and in the whole Sura. Through this method of interpretation, Johns succeeded in discovering many novel meanings of narrative verses of the Quran not found out by using any other method. This work wanted to elaborate much on Johns study and showed some fortune and possibilities in using this method in understanding the meaning of the Quran, especially of its narrative verses.